Social support, academic self-concept, academic motivation, university environment, academic aspirations, mentor scale, education goals, decision to study, and soft skills: a case of residential college students of UiTM - Othman, Nasuddin; Noordin, Fauziah; Mat Nor, Norzana; Azmi, Azida; Wan Abd Rahim, Wan Ahmad Rahiman; Yaacob, Azizah; Endot, Zaiton (2011)
The objectives of this study are to assess the level of perceived social support appraisal, academic self-concept, academic motivation, perceived university environment, academic, mentor scale, students' perception on decision to attend university, educational goals, and soft skills of the students of the residential colleges in UiTM. In addition, it is hoped that the findings of this study would provide practical information for university administrators, college administrators, and students with recommendations for improvement purposes. Questionnaires were distributed to a total of 3,050 students from various colleges who have agreed to participate in the research project. From the total of 3,050 completed questionnaires, only 2,918 sets of the questionnaires were useable. This gave a response rate of 95.67%. The findings indicate that family acts as the main social support for the respondents, the respondents have high self-concept with regard to their ability to excel in the studies, the residential colleges students obtained their academic motivation mostly from the family, i.e., primary and secondary, the results noted that more that 50 percent of the respondents' guardian did not graduate from university and/or college, moderate perception on the university environment, residential college students were reported to aim for the highest degree, i.e., Master Degree and also aspired to complete their current degree. This is an indication that the respondents aspire to pursue their educational to a higher level than what they are at currently. The findings also indicate that the respondents regard their friends and family members as mentor as and it appears that they do not have many people in the university whom they regard as their mentors. It appears that respondents understood what their educational goal was and they perceived that their parents supported their their career/academic programme and they knew the importance of getting a tertiary education for their future career purposes. Finally, the lowest mean value of 3.17 for the statement "I prefer to be just a follower than a leader" stated in the soft skill section of the questionnaire is a very significant finding and the management the university has to seriously deal with this issue of students preferring to be followers rather than leaders. This is an area where the management of UiTM need to investigate further to determine the reasons or factors that led to these results. The findings of this study may serve as a needs assessment for the management of the university so that they can work with the residential college administrators to create appropriate intervention programmes and advocate for change in policies that impact the residential college students' university life.